1960
DOI: 10.1002/art.1780030402
|View full text |Cite
|
Sign up to set email alerts
|

Sjogren's syndrome I. Serologic reactions in patients with Sjogren's syndrome with and without rheumatoid arthritis

Abstract: a I of t he g m eri cun R lieu ma t ism d ssociu tion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1962
1962
1971
1971

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Recent work (Anderson et al, 1957;Blizzard et al, 1962) shows that atrophic adrenalitis has an autoimmune component, and it has been known for many years that patients with Addison's disease have an increased incidence of focal thyroiditis. The serological overlap between thyroiditis and Sjdgren's syndrome (Bloch et al, 1960;Anderson et al, 1961), and also that between discoid L.E. and thyroid autoimmunity (Shrank and Doniach, 1963) (Stanbury and Chapman, 1960).…”
Section: Organ-specificitymentioning
confidence: 99%
“…Recent work (Anderson et al, 1957;Blizzard et al, 1962) shows that atrophic adrenalitis has an autoimmune component, and it has been known for many years that patients with Addison's disease have an increased incidence of focal thyroiditis. The serological overlap between thyroiditis and Sjdgren's syndrome (Bloch et al, 1960;Anderson et al, 1961), and also that between discoid L.E. and thyroid autoimmunity (Shrank and Doniach, 1963) (Stanbury and Chapman, 1960).…”
Section: Organ-specificitymentioning
confidence: 99%
“…Antiglobulins have been noted in a number of varied diseases including rheumatoid arthritis [14], liver disease [15], col lagen vascular disease [16], lues [17], sarcoidosis [18], leprosy [19].…”
mentioning
confidence: 99%
“…In addition, the serologic factors of rheumatoid arthritis are present as often in Sjo gren's syndrome as they are in RA itself. Bloch et al (165) demonstrated rheumatoid factor in 90 per cent of 21 patients with the syndrome, and in 75 per cent of patients with Sjogren's syndrome without joint involvement. Antinuclear antibody was also present in 71 per cent of their patient group.…”
Section: Other Diseasesmentioning
confidence: 97%
“…Bloch et al (165 ) reported that 90 per cent of 21 patients with Sjogren's syndrome had rheumatoid factor, 71 per cent hypergamma globulinemia, 71 per cent antinuclear factor, and 10 per cent the LE cell phenomenon. The direct Coombs test was positive in 25 per cent of the group.…”
Section: Interrelationships With Other Mesenchymal Diseasesmentioning
confidence: 98%